Maintenance, a Forgotten Part of the Strategic Plan - Riva Zaferson, Franco Alberto (2017)
This article exposes the reasons behind the relegation of maintenance management as an operative unit instead of a strategic tool in the organizational management. It works with literature review and the peruvian business context. Finally, it shows some statistical criteria relevant to the maintenance planning.